Bahan Ajar e-LKPD Berbasis Live Worksheet Pada Pembelajaran IPA untuk Siswa Kelas V Sekolah Dasar - Ignasia Erlina; Ni Ketut Suarni; Ndara Tanggu Renda (Journal for Lesson and Learning Studies, 2022)
The use of teaching materials in the form of books commonly used in learning causes learning activities to become monotonous. The availability of attractive teaching materials can affect students' attention to be active in learning. The purpose of this study is to create e-student worksheet teaching materials based on Live Worksheet in science learning. This type of research is development research based on the ADDIE model. The subjects of this study consisted of three media experts, two material experts, two practitioners, and 12 students to test student responses. The data collection method in this study applies a questionnaire method with a rating scale instrument as a data collection instrument. The data analysis technique used is descriptive qualitative and quantitative analysis techniques. The data obtained were then analyzed to calculate internal validity and empirical validity. The results of the internal validity analysis are in the valid criteria. The average score of the empirical validity assessment is in the very valid criteria. Based on the analysis results, the e-LKPD teaching materials based on the Live Worksheet on the water cycle material science content are valid and well applied to the learning process.